Elements in developing the psychosocial training Manual (PsyCoT-M) for volunteers in Malaysia context - Kamsani, Siti Rozaina; Ishak, Noor Azniza; Mustaffa, Jamaludin; Ibrahim, Nabisah (Institute of Advanced Scientific Research, 2019)
One of the agenda in National Transformation Policy is to transform the social developmental program among Malaysian population. In line with this agenda, most of the non-government agencies have designed many volunteer activities and programs that involved by the Malaysian community. These kind of programs would instill the volunteerism spirit among Malaysian people. So that, volunteering is an emerging and positive trend for Malaysian. The experience from the various type of disasters has shown that volunteers are often the only readily available human resource for psychosocial response in a disaster situation. Unfortunately, those who are involved with these volunteer activities are not equipped with specific training such as psychosocial training. Therefore, the purpose of this research is to examine the elements of the psychosocial training that meet the individual and community needs in the Malaysia context.Out of 10 professional and non-professional volunteers who were voluntary participation in focus group technique. This study is a pioneering attempt to contribute towards improvement the volunteer training skills among the young generation by promoting and improving the quality of volunteer services in Malaysia.